APLIKASI DATA MINING UNTUK PERBANDINGAN MANAJEMEN LABA TERHADAP TINGKAT RESIKO INVESTASI PADA PERUSAHAAN PERBANKAN DI INDONESIA STOCK EXCHANGE - Prajana, Andika (International Journal of Natural Science and Engineering, 2017)
The financial report is a means of communicating financial information to parties outside the corporation. The preparation of financial statements, an accrual basis was chosen because it is more rational and fair in reflecting the company's financial condition in real terms, but the other can use the accrual basis to the management to provide more flexibility in choosing accounting methods for not deviate from the rules applicable Financial Accounting Standards. In this study, comparative analysis Persistency Profit Management with Investment Risk level by applying the Application of Data Mining with Rough Set Theory in order to find a pattern or knowledge that can be used as a basis to predict what action will be performed in managing earnings management and banking conditions in company's future.